Diameter-selective extraction of single-walled carbon nanotubes by interlocking with Cu-tethered square nanobrackets - Cheng, Guoqing; Komatsu, Naoki (Beilstein Journal of Organic Chemistry, 2024)
We have been working with carbon nanotube separation through host–guest chemistry. Herein, a new macrocyclic host molecule, Cu-tethered square nanobrackets, is designed, synthesized and applied to single-walled carbon nanotubes (SWNTs) for their diameter-based separation. The complexation between copper ions and dipyrrin moieties of the nanobracket gives Cu-tethered square nanobrackets, which is confirmed by absorption, Raman and MALDI-TOF mass spectra. Upon extraction of SWNTs with the nanobracket and copper(II), in situ-formed square Cu-nanobrackets are found to interlock SWNTs to disperse them in 2-propanol. The interlocking is confirmed by Raman spectroscopy after thorough washing of the extracted SWNTs. Pristine SWNTs were recovered through demetalation of the interlocked ones along with the nanobracket. Raman and absorption spectroscopies of the extracted SWNTs reveals the diameter enrichment of only several kinds of SWNTs in the diameter range from 0.94 to 1.10 nm among ≈20 kinds of SWNTs from 0.76 to 1.20 nm in their diameter range. The diameter selectivity is supported by the theoretical calculations with the GFN2-xTB method, indicating that the most preferred SWNT diameter for the square Cu-nanobrackets is 1.04 nm.
Keywords: complexation; diameter; extraction; interlock; nanobracket; single-walled carbon nanotubes; separation